Investigating Viral Inoculation and Recovery from Medical Masks - Mark C. Wilkinson; Jennifer Carney (Advances in Virology)
The SARS-CoV-2 pandemic from 2019 onwards has significantly increased the usage of surgical style medical masks, both in healthcare and public settings. It is important to study the contamination of and viral transfer from such masks. However, accepted standard test methods such as ISO 18184 have prescribed inoculation methods which may not be fully representative of the type of viral insult experienced in the clinic or community. In addition to studying a conventional mask, the performance of a mask featuring an antimicrobial photosensitiser was also studied.